2001
DOI: 10.1002/1521-3765(20011203)7:23<5099::aid-chem5099>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Figure-Eight Tetrathiaoctaphyrin and Dihydrotetrathiaoctaphyrin

Abstract: The acid-catalyzed condensation of pyrrole and 2,5-bis(p-tolylhydroxymethyl)thiophene yields two novel giant heteroporphyrins: 5,10,15,20,25,30, 35,40-octa(p-tolyl)-41,43,45,47-tetrathia[36]octaphyrin(1.1.1.1.1.1.1.1) (S4OP) and 5,10,15,20,25,30,35,40-octa(p-tolyl)-dihydro-41,43,45,47-tetrathia[38]octaphyrin(1.1.1.1.1.1.1.1) (S4OPH2). These tetrathiaoctaphyrins are interconvertible through dihydrogenation or dehydrogenation processes. Both compounds possess helical figure-eight geometry with two thiophene ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 74 publications
1
58
0
4
Order By: Relevance
“…They found that hydrogen bonding is effective for the development of Huckel antiaromatic expanded porphyrins. The molecular framework of octaphyrin is consistent with a 36 π-electron circuit within what can be considered a twisted double-side (orientable) Huckel topology (Sprutta and Latos-Grazyński, 2001; Flemming and Dolphin, 2002; Pushpan et al, 2002; Silva et al, 2002a,b; Hata et al, 2006). According to Osuka et al the hydrogens present near the crossing point of the octaphyrin resonate at δ = 17.14 and 8.60 ppm in the deshielding region.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…They found that hydrogen bonding is effective for the development of Huckel antiaromatic expanded porphyrins. The molecular framework of octaphyrin is consistent with a 36 π-electron circuit within what can be considered a twisted double-side (orientable) Huckel topology (Sprutta and Latos-Grazyński, 2001; Flemming and Dolphin, 2002; Pushpan et al, 2002; Silva et al, 2002a,b; Hata et al, 2006). According to Osuka et al the hydrogens present near the crossing point of the octaphyrin resonate at δ = 17.14 and 8.60 ppm in the deshielding region.…”
Section: Introductionmentioning
confidence: 57%
“…The discovery of sapphyrins and expanded porphyrins have attracted the interest of researchers attributed to their diverse applications in materials science (Sprutta and Latos-Grazyński, 2001; Flemming and Dolphin, 2002; Pushpan et al, 2002; Silva et al, 2002a,b; Cavaleiro et al, 2003; Hata et al, 2006; Tanaka and Osuka, 2016). The defining feature of these macrocycles is the presence of a larger internal cavity as compared to those present in natural tetrapyrroles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The condensation reaction of 2,5-bis(p-tolylhydroxymethyl) thiophene and pyrrole under acid catalysis yielded A and B in 2% yield (figure 11). Exposure of A to NaBH 4 in THF transformed to B.…”
Section: Porphyrin Based Systemsmentioning
confidence: 99%
“…Usually all expanded porphyrins show broad 1 H resonance signals at room temperature, which is difficult for further progression of study [16] in the molecule. The broadening in the NMR spectrum at normal temperature is due to rapid rotation of the heterocyclic rings and at low temperature the rate of rotation is reduced relative to the NMR timescale [17].…”
Section: Strategy For the Nmr Assignments And Dynamic Study Of The Exmentioning
confidence: 99%